Experimentation of the Flipped Classroom Learning Model Based on Student's Self-Regulated Learning - Zainnur Wijayanto; Sukestiyarno Sukestiyarno; Kristina Wijayanti; Emi Pujiastuti (International Conference on Science, Education, and Technology, 2022)
A flipped classroom is an innovative approach that focuses on student centered learning. It swaps the arrangement of knowledge different from traditional classroom. This study aims to describe the learning outcomes of SMP Negeri 1 Sewon students in which learned using Flipped Classroom Learning Model comparing to the Direct Learning Model, and to find out whether the flipped classroom learning model is effectively used in mathematics learning. This is quasi-experimental research. The research subjects were divided into 2 groups, namely the experimental group (using flipped classroom learning model) and control group (using direct learning model). The results showed that the flipped classroom learning model was more effective than direct learning model in terms of its self-regulated learning (SRL). It can seem from the results of statistic data analysis which shows a significant difference. So, it can be concluded that flipped classroom model can be used as an alternative learning in the classroom.